Knowledge, Leadership, and Experience: Determinants of Patient Safety Culture - Ni Luh Putu Asrini Dewi; Endang Suswati; Sugeng Mulyono (LPPM STIE KRAKATAU, 2026)
Patient safety culture is a critical component of healthcare quality and is influenced by both individual and organizational factors. This study examines the roles of knowledge level and leadership style in shaping patient safety culture, while considering length of service (tenure) as an intervening variable. A quantitative explanatory design was employed using structural equation modeling-partial least squares (SEM-PLS). The study involved 40 healthcare professionals (doctors, nurses, and midwives) at Permata Husada Pleret Hospital, Yogyakarta, who were selected using total sampling. Data were collected using validated questionnaires and analyzed to assess the direct and indirect relationships among the variables. Knowledge level (β = 0.312; p < 0.05) and leadership style (β = 0.354; p < 0.05) significantly influenced patient safety culture. Length of service (tenure) also had a significant effect (β = 0.267; p < 0.05). The indirect effects indicate that tenure partially transmits the influence of knowledge (β = 0.077; p < 0.05) and leadership (β = 0.080; p < 0.05) on patient safety culture. The model explained 60.0% of the variance in patient safety culture (R² = 0.600), indicating moderate-to-strong explanatory power. Patient safety culture is shaped by the combined influence of knowledge, leadership and tenure. However, tenure should be interpreted cautiously as organizational exposure rather than purely experiential learning. Given the small sample size and single-hospital setting, the findings should not be generalized. Future studies should incorporate larger, multicenter samples to improve external validity.